Pengaruh Manajemen Talenta dan Lingkungan Kerja Non Fisik Terhadap Retensi Karyawan - Novita Sari; R. Deni Muhammad Danial; Resa Nurmala (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Liza Christina Garment Industry is a company engaged in the manufacture of taxtiles or apparel that has problems with employee retention. This study aims to dtermine whether the application of talent management and non-physical work environment has an influence and can improve employee retention of PT. Liza Christina Garment Industry Sukabumi. The reseach method used is quantitative method with descriptive approach and asssosiative analysis. The sampel in this study was 48 respondents who were permanent employees of PT, Liza Christina Garment Industry Sukabumi using saturted sampling technique. Data were obtained through a research quastionnaire distributed to all samples containing 27 statements regarding talent manajemen variables, non-physical work environment and employee retention, using a semantic differential measurement system. The data obtained will bw sybjected to various test such as validity and reliability test, as well as classical assumption test which are then analyzed with various test assisted by SPSS 25 sofhware in an effort to answare the hypotesis in this study. The result showed that there was a positive and significant influence between talent management on employee retention, and there was a positive and significant influence between non-physical work environment variables on employee retention simultaniously PT. Liza Christina Garment Industry Sukabumi